Field Efficacy of Steinernema Carpocapsae Against Lima Bean Pod Borer, Etiella zynckenella Treitschke, Attacking Groundnut - Apriyanto, Dwinardi; Nadrawati, -; Sunardi, Tri; Suryati, Dotti (International Journal on Advanced Science, Engineering and Information Technology, 2016)
Lima bean pod borer (LBPB), Etiella zynckenella Trietschke, is major insect pest of soybean in Indonesia. Currently it was also reported attacking groundnut in some parts of Sumatera causing serious yield loss. Insecticide treatment is not only ecologically unsafe, but also is not practical due to concealed behavior of the larvae within pods below soil surface. Systemic insecticide might be so but unsafe as it might leave unaccepted residue in harvested pods. It is clear that safer more effective technology such as biological control is badly needed. A Field study was conducted at the University of Bengkulu Research Station in 2012-2013. The objectives was to determine the effectiveness of non local strain of entomopathoegen nematode (EPN), Sterinenema carpocapsae, to control LBPB attacking groundnut. Groundnut seeds were sewed in plots which were later treated with S. carpocasae produce by Biological Control Laboratory University of Jember at the dose of 500.000 JI m-2. EPN was sprayed upon plants and soil surface twice at plant age of 45 and 65 days after sewing (DAS). There were insecticide treatment and control plots as comparison. Observations of damaged pods and the presence of LBPB larvae were done at plant age of 63, 77, 90 DAS and at the haevesting date. Data were subjected to analysis of variance and the means of damaged pods were separated with least significant different (LSD). The result revealed that in two years study, damaged pods consistently tended to be less in plots treated with S. carpocasae or insecticide than those in controls, indicating that it might be effective against PLPB. The lack of significant different between EPN treated and control plots might be as a result of low percentages of EPN larval survival due shipment problem (i.e. inappropriate packaging and long transportation that toke several days) or it might be that the strain was less adapted yet to local conditions. I speculate that local strain of EPN might be more effective to control LBPB attacking groundnut.